Initial heifer body composition has little impact on response to Zilmax - Thompson, L.K.; Schneider, C.; Parsons, G.; Miller, K.; Reinhardt, Christopher D.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Using a growth promotant at the correct time of finishing is critical for maximizing profit potential. Previous studies have shown that zilpaterol-HCl (Zilmax; Intervet/ Schering-Plough Animal Health, Millsboro, DE) improves carcass characteristics. The objective of this study was to determine effects of prior body composition on subsequent changes in carcass weight, fatness, and muscle in heifers fed Zilmax so producers can introduce Zilmax at the level of finish that will result in the most desirable response. We hypothesized that fatter heifers use fat as the fuel for muscle growth.
Keywords: Beef; Heifer; Zilmax; Growth promotant